Duality of Paleo- and Neoarchean metamorphism as recorded in disparate Eoarchean (pre-3700 Ma) sedimentary protoliths - Tropper, Peter; Peine, J.; Schmitt, Axel Karl; Mojzsis, S. J.; Manning, C. E. (Lithos, 2025)
The oldest supracrustal belts are our best archives of early surficial processes; two well-known ancient examples occur in southern West Greenland (Færinghavn terrane) and northern Québec (Inukjuak domain). Despite their widespread interest, the metamorphic histories of these rocks are little constrained. Previous work on the Akilia (sample GR114 from Manning et al., 2006) and Innersuartuut islands (sample GR27b from Cates and Mojzsis, 2006), Færinghavn supracrustal enclaves reported minor anthophyllite-garnet rocks with rare metamorphic zircons yielding common UPb core ages of ca. 3650 Ma and rim ages at ca. 2700 Ma. The main mineral assemblages comprise garnet + anthophyllite + hornblende + biotite + plagioclase + K-feldspar + quartz. Secondary biotite and plagioclase with diffusive modification of the garnet compositions along fractures points to a later metamorphic overprint. Our new phase equilibrium calculations of the main matrix assemblage yield average P-T conditions (± 1σ) of 580 ± 40 °C and 0.6 ± 0.1 GPa for both Akilia and Innersuartuut. Zr-in-rutile geothermometry of rutile inclusions in garnet from an Akilia sample (GR114) shows increasing T from 610 ± 30 °C (core) to 670 ± 30 °C (rim). Rutile UPb geochronology yields discordant ages (± 1σ) ranging from 2410 ± 56 Ma to 1383 ± 78 Ma: the upper intercept age of 2542 ± 214 Ma overlaps with uncertainties previously reported UPb zircon rim ages around 2700 Ma and a lower intercept at 1014 ± 237 Ma points to a Grenville/Sveconorwegian orogen overprint. An Inukjuak domain coarse-grained quartzite (sample IN14032 from Greer et al., 2022) contains several different zircon age populations; the oldest (detrital) zircons have a weighted average 207Pb/206Pb age of 3736 ± 5 Ma. Two younger, smaller, zircon populations cluster around 3650 Ma and ca. 2700 Ma. The main mineral assemblage is anthophyllite + muscovite + quartz + rutile. Former biotite is replaced by stilpnomelane, and anthophyllite is replaced by chlorite + talc. Pervasive greenschist-facies retrogression of the sample prevents the calculation of P-T conditions using phase equilibrium calculations. Zr-in-rutile geothermometry limits T at an assumed pressure (0.6 GPa) to 670 °C ± 20 °C (± 1σ). Rutile UPb geochronology yielded 2538 ± 10 Ma, an age which correlates well with the youngest zircon age cluster, consistent with the lower closure T for Zr diffusion in rutile (<600 °C). The Færinghavn and Inukjuak supracrustal rocks experienced synchronic Neoarchean metamorphism at analagous upper amphibolite-facies conditions (580-670 °C). Our P-T data agree very well with intermediate thermal dT/dP gradient from the literature that are typical for the Neoarchean geodynamic setting of paired metamorphic belts. Evidence of for a high-greenschist-lower amphibolite-facies overprint during the Late Proterozoic Grenville/Sveconorwegian event is present in the Færinghavn terrane, but not the Inukjuak domain.
Online verfügbar: 7. März 2025, Artikelversion: 11. März 2025
Gesehen am 19.08.2025